Pilgrim Law: Overcoming False Consciousness through the Witness of London's Economic Migrants - Rougeau, Vincent D. (Journal of law and religion, 2007)
It is both an honor and a pleasure to be asked to participate in this festschrift for my friend and colleague, Robert E. Rodes, Jr. Since I joined the Notre Dame Law School faculty in 1998, Bob has been an inspiration to me in so many different ways, and in my opinion, he exemplifies the best tradition of an American man of letters. It is a rare American law school that can boast a faculty member whose interests range from medieval French and English law to modern civil procedure, legal ethics, poverty law and liberation theology. But we at Notre Dame have all this in Bob, and it is through these wide-ranging interests that I found not only intellectual common ground with him, but also a mentor and a friend.It just so happens that Bob and I received our undergraduate and law degrees from the same institutions, Brown University and Harvard Law School. Although our experiences at both places were separated by almost forty years, I like to think that our shared educational provenance links us in a special way. In addition, for the last five years or so, we have belonged to the same parish and, more often than not, we attend the same mass. This has offered our professional relationship the wonderful counterpoise of the fellowship of our parish community, and it has given me and my wife, Robin, a chance to spend more time with Bob's delightful wife Jeanne, to whom he has been married over fifty years.